UPAYA KONSERVASI JALAK BALI (Leucopsar rothschildi) MELALUI KEARIFAN LOKAL MASYARAKAT BALI - kadek yuniari suryatini; Ni Made Milati (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2024)
Bali starling (Leucopsar rothschildi) is one of the endemic species of Bali and the typical Indonesian animal whose natural distribution is only found in the Bali Barat National Park. The number of Bali starlings in nature is few and are classified as rare or endangered animals. This is the effect of the large number of illegal hunts in natural habitats because of high market demand and loss of forest habitat which causes the population of Bali starlings to decline rapidly. The method used in this research is library research with a qualitative descriptive approach. Based on the research results, it is known that conservation efforts for the Bali starling as a protected animal through the local wisdom of the Balinese people which is based on the Tri Hita Karana philosophy have had a positive influence on the number of Bali starlings. The explanation of Tri Hita Karana is in the form of awig-awig or customary law. Community support for local wisdom is important in its implementation in a conservation-carrying capacity.